Acute Systemic Organ Injury in Term Infants with Perinatal Asphyxia: Acute Systemic Organ Injury with Perinatal Asphyxia - Hussain, Tariq; Rehman, Sijad Ur; Inayatullah, .; Gul, Haji; Hussain, Saddam; Haris, Muhammad (Pakistan Journal of Health Sciences, 2025)
Perinatal asphyxia is a major contributor to neonatal morbidity and mortality. This leads to multiple organ dysfunction (MODS). Objectives: To assess the extent of acute organ system injury in term newborns with perinatal asphyxia, focusing on clinical and biochemical markers indicative of MOSD. Methods: This descriptive cross-sectional study involved 50 term newborns diagnosed with perinatal asphyxia. Clinical manifestations and biochemical markers, including renal and liver function tests, were analyzed to evaluate the extent of organ dysfunction. Fifty term newborns diagnosed with perinatal asphyxia were enrolled through non-probability convenience sampling. Clinical assessments included evaluations of the neurological, cardiovascular, respiratory, renal, and hepatic systems. Biochemical tests measured serum creatinine, serum ALT, and CKMB levels to assess kidney, liver, and myocardial function, respectively. Data were analyzed using descriptive statistics and Chi-square tests to examine the relationship between perinatal asphyxia and multi-organ injury, with a significance level of p≤0.05. Results: The severity of perinatal asphyxia was significantly correlated with the incidence of organ damage. Serum creatinine levels were elevated in 18 (36%) neonates, ALT levels were elevated in 20 (40%) neonates, and CKMB levels were elevated in 23 (46%) neonates. In some cases, early intervention was linked to improved neurological outcomes. Conclusions: This study emphasizes the critical need for early diagnosis and prompt intervention to prevent extensive organ damage in newborns with perinatal asphyxia. The severity of organ dysfunction is closely related to the degree of asphyxia, highlighting the importance of comprehensive monitoring and targeted treatment strategies. Further research is essential to develop better protective interventions for these infants.